2007
DOI: 10.1093/jee/100.3.847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Particle Film on Biology and Behavior of Diaphorina citri (Hemiptera: Psyllidae) and Its Infestations in Citrus

Abstract: Studies were conducted to investigate the effects of a kaolin-based hydrophilic particle film, Surround WP, on the biology and behavior of the psyllid Diaphorina citri Kuwayama (Hemiptera: Psyllidae) and to assess population densities of D. citri in citrus subjected to monthly applications of Surround WP. Laboratory investigations indicated a 3% (wt:vol) suspension of Surround WP in water applied directly was not acutely toxic to eggs, older nymphs or adults. Presence of the dried particle film on leaves inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 0 publications
2
54
1
8
Order By: Relevance
“…Joubert et al (2004) found that Surround WP treatments caused mild repercussions for mango scale. For S. oleae, it is possible that a difficulty to grasp or move occurs, as has been reported for other insect species (Glenn et al 1999;Puterka et al 2005;Hall et al 2007); this difficulty may cause the insects to fall down and not find the right site for establishment.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Joubert et al (2004) found that Surround WP treatments caused mild repercussions for mango scale. For S. oleae, it is possible that a difficulty to grasp or move occurs, as has been reported for other insect species (Glenn et al 1999;Puterka et al 2005;Hall et al 2007); this difficulty may cause the insects to fall down and not find the right site for establishment.…”
Section: Discussionmentioning
confidence: 89%
“…Processed kaolin has been reported to effectively control different species of psyllids (Puterka et al 2000Glenn and Puterka 2005;Saour 2005;Hall et al 2007). However, in our study, Surround WP treatment did not have any effect on the numbers of E. olivina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hall et al (2007) body size can be an important factor when assessing the effects of particle films on mortality among species. Considering body size of spider and fly, the former is considerably bigger than the latter, and this ratio spider/fly increases through the assay.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, kaolin is a white aluminosilicate mineral clay, chemically inert over a wide pH range that has been widely used in a variety of industrial applications, including paints, cosmetics, pharmaceuticals and agriculture (Glenn et al, 1999;Glenn and Puterka, 2005;Knight et al, 2000). The interest for this natural substance is reflected in the number of works covering different crops such as pear Daniel et al, 2005), apple (Knight et al, 2001;Friedrich et al, 2003), olive (Pascual et al, 2010), walnut and almond (Rosati et al, 2006), citrus (Hall et al, 2007), wine grape (Glenn et al, 2010), pecan (Cottrell et al, 2002), cotton (Showler, 2003;Silva and Ramalho, 2012), tomatoes (Kahn and Damicone, 2008) and cabbage (Alavo and Abagli, 2011). In general, those and other studies showed kaolin as an effective substance in reducing the population of several groups of pests, such as Hemiptera (Daniel et al, 2005;Alavo and Abagli, 2011;Martinou et al, 2014), Lepidoptera (Showler, 2003;Sackett et al, 2007), Diptera (Mazor and Erez, 2004;Pascual et al, 2010) and Coleoptera (Silva and Ramalho, 2012).…”
Section: Introductionmentioning
confidence: 99%